Developing Pure Cartoon for Stoichiometry Concept Combined with Guided Inquiry to Improve Process Skill and Students’ Learning Outcome - Fatma Al Hamid (JPP (Jurnal Pendidikan dan Pembelajaran))
Abstract: This research aims at improving processing skills and learning outcome of students on stoichiometry concept. First stage was instructional instrument development, the second stage was trials on X graders of Senior High School using One Group Pre-test and Post-test Design. The results of this research showed that (1) the developed instructional instrument is good and reliable, (2) the lesson plan was well-accomplished, (3) students activity were positive during the learning, (4) students response were positive, (5) the cognitive learning iutcomes of product and process have met minimum criteria of mastery learning, (6) the improvement of processing skill is in the category of high gain. To sum up, the developed instructional instrument could improve students processing skill and learning outcomes.